Detection and characterization of lipids in eleven species of fish by non-targeted liquid chromatography/mass spectrometry. (1st November 2022) - B. Gowda, Siddabasave Gowda; Minami, Yusuke; Gowda, Divyavani; Chiba, Hitoshi; Hui, Shu-Ping
Graphical abstract: Highlights: Lipidome in eleven dietary fish was investigated. A total of 287 molecular species from five major lipid classes were characterized. Multivariate analysis revealed lipid composition specific clustering in each fish type. N -acyl lysophosphatidylethanolamines are identified for first time in fish fillets. The assessment of nutritional indices suggested shishamo smelt is highly beneficial for health. Abstract: Fish is an important nutrition source because its lipids, which are rich in ω-3 fatty acids, are beneficial for human health. However, studies focusing on their detection, composition, and nutritional value are limited. In this study, we applied a non-targeted lipidomic approach based on ultra-high performance liquid chromatography coupled with linear-ion trap-Orbitrap mass spectrometry (UHPLC/LTQ-Orbitrap-MS) to comprehensively profile, compare, and detect unknown lipids in eleven types of dietary fish. A total of 287 molecular species from five major lipid classes were characterized by MS/MS analysis. Multivariate principal component analysis revealed the distinct lipid composition in shishamo smelt and Japanese sardine compared to other fish types. The assessment of nutritional indices based on the levels of free fatty acid suggested that among the eleven fish types, shishamo smelt is highly beneficial for health. Further, lipids such as N -acyl lysophosphatidylethanolamine were detected and characterized for the first time in fish fillets. Hierarchical cluster correlations indicated the predominance of glycerophospholipids (GPs) and sphingolipids in sardine, whereas fatty acyls and triacylglycerols (TAGs) were predominant in shishamo smelt. The high levels of polyunsaturated fatty acid-enriched GPs and TAGs in dietary fish endow it with great potential as a health-promoting food for human consumption. This study offers a comprehensive analysis of lipids and their compositions in fish fillets, demonstrating their potential use in the nutritional assessment of functional foods.